Dexmedetomidine Ameliorates Sleep Deprivation-Induced Depressive Behaviors in Mice - Eun-Jin Moon (International Neurourology Journal, 2018)
Purpose Sleep deprivation induces depressive symptoms. Dexmedetomidine is a α2-adrenoreceptor agonist and this drug possesses sedative, anxiolytic, analgesic, and anesthetic-sparing effect. In this study, the action of dexmedetomidine on sleep deprivation-induced depressive behaviors was investigated using mice. Methods For the inducing of sleep deprivation, the mice were placed inside a water cage containing 15 platforms and filled with water up to 1 cm below the platform surface for 7 days. One day after sleep deprivation, dexmedetomidine at the respective dosage (0.5, 1, and 2 μg/kg) was intraperitoneally treated into the mice, one time per a day during 6 days. Then, forced swimming test and tail suspension test were conducted. Immunohistochemistry for tyrosine hydroxylase (TH), 5-hydroxytryptamine (5-HT; serotonin), tryptophan hydroxylase (TPH) and western blot for D1 dopamine receptor were also performed. Results Sleep deprivation increased the immobility latency in the forced swimming test and tail suspension test. The expressions of TPH, 5-HT, and D1 dopamine receptor were decreased, whereas, TH expression was increased by sleep deprivation. Dexmedetomidine decreased the immobility latency and increased the expressions of TPH, 5-HT, and D1 dopamine receptor, whereas, HT expression was decreased by dexmedetomidine treatment. Conclusions In our results, dexmedetomidine alleviated sleep deprivation-induced depressive behaviors by increasing 5-HT synthesis and by decreasing dopamine production with up-regulation of D1 dopamine receptor.